QoS-Aware Middleware for Ubiquitous Environment: A Review and Proposed Solution. (19th March 2014) - Al-Roubaiey, Anas; Alkhiaty, M. AL-Rhman
Abstract : Ubiquitous computing has introduced a new era of computing. Compared to traditional distributed systems, ubiquitous computing systems feature increased dynamism and heterogeneity. In traditional computing environments (mainframe and PC), users actively choose to interact with computers. Ubiquitous computing applications are likely to be different, where computing systems are available anywhere but not visible. The underlying ubiquitous computing infrastructures are more complex and bring up many issues. In this work we survey the literature to demonstrate, in detail, the characteristics and the challenges of the ubiquitous computing as well as the requirements for building ubiquitous software that brings these characteristics into reality. Furthermore we present some existing middleware solutions for ubiquitous environments, and propose our middleware-based architecture to facilitate the user interaction in such environment. To the best of our knowledge this is the first work proposing DDS-based solution for ubiquitous computing as a unified middleware.